Little Chick - Hest, Amy.; Jeram, Anita (Somerville, Mass. : Candlewick, 2009)
A collection of three stories in which Little Chick learns how to deal with life's disappointments with the help of his beloved auntie.
Bulletin of the Center for Children's Books starre.
Pub Weekly.
School Library Journal starred.
1.6
K-3
Keywords: Aunts -- Juvenile fiction; Chicks -- Juvenile fiction; Animals -- Infancy -- Fiction; Aunts -- Fiction; Chickens -- Fiction; Animal babies -- Fiction; Aunts -- Fiction; Chickens -- Fiction